Kilometres 51 and 101: the development of Soviet residency and banishment policies in Ukraine, 1917-1940 - Vronska, T; Stiazhkina, O; Jones, P (Taylor and Francis, 2024)
This article analyses the evolution of spatial constraints around Soviet cities and other sensitive zones, especially in Ukraine and Russia, arguing that banishment and residency prohibition was a consistent and significant element of Bolshevik policy from the revolution onwards, and not just from the start of passportisation of the early 1930s. It traces the development of legislation and extra-legal practices that led to the banishment and barring of multiple (and ever-increasing numbers of) categories of citizens from Russian and Ukrainian metropolitan areas and the zones around them, and also from other zones deemed to be in need of special protection. The article also traces the particular constellation of anxieties about nationalism, the peasantry and the border, which made Ukraine proportionally the most spatially restricted Soviet republic during Stalinism.